Are there Possibilities for Synthesis of Theories of Nationalism and Ethnicity - Statkus, Nortautas (Sociologija. Mintis ir veiksmas, 1998)
The aim of the article is twofold. First, it aims at an overview and a critical evaluation of the main theories of ethnicity and nationalism. Second, it attempts to define the possibilities of their synthesis. The author argues for an understanding of ethnicity as a complex phenomena, whose explanation is connected with a interaction of genetic, psychological, social and cultural factors. Nationalism is defined as political ideology which develops as a result of the processes of modernization and holds an idea of political soveireignity of ethnic groups.